First Case Report of Maturity-Onset Diabetes of the Young Type 4 Pedigree in a Chinese Family - Deng, Mingqun; Xiao, Xinhua; Zhou, Liyuan; Wang, Tong (Frontiers in Endocrinology, 2019)
Maturity-onset diabetes of the young (MODY) is the most common monogenetic diabetes, which is easily misdiagnosed. We describe the first Chinese MODY4 family with a novel mutation, indicating that MODY4 cannot be excluded in early-onset obese diabetes, and pancreatic exocrine dysfunction could be present in MODY4.